2008
DOI: 10.1002/jmri.21378
|View full text |Cite
|
Sign up to set email alerts
|

3D dynamic contrast‐enhanced MRI of rectal carcinoma at 3T: Correlation with microvascular density and vascular endothelial growth factor markers of tumor angiogenesis

Abstract: Purpose:To determine how dynamic contrast-enhanced (DCE) MRI at 3T correlates with rectal carcinoma angiogenesis. Materials and Methods:Three-dimensional (3D) DCE MRI was performed in 38 patients (23 males, 15 females, mean age 60 years) with histologically-confirmed rectal carcinoma at 3T. Time-intensity curves (TICs) were used to measure peak enhancement ratio (ER peak ), time to peak enhancement (T peak ), first enhancement time (T first-enhance ), and uptake rate for rectal tumor, normal rectal wall, and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 26 publications
5
51
0
Order By: Relevance
“…There have been two prior studies on quantitative DCE MRI of prostate cancer before and after ADT (17,19), and one study investigating semiquantitative DCE MRI combined with MR spectroscopy (20), however none of these studies incorporated DW MRI. DCE MRI has been validated as a surrogate marker of tumor angiogenesis in prostate cancer and other primary tumors (21,22). In murine models, androgen ablation has been shown to suppress the production of the angiogenic factor VEGF (vascular endothelial growth factor) by the glandular epithelium and induce apoptosis of endothelial cells (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…There have been two prior studies on quantitative DCE MRI of prostate cancer before and after ADT (17,19), and one study investigating semiquantitative DCE MRI combined with MR spectroscopy (20), however none of these studies incorporated DW MRI. DCE MRI has been validated as a surrogate marker of tumor angiogenesis in prostate cancer and other primary tumors (21,22). In murine models, androgen ablation has been shown to suppress the production of the angiogenic factor VEGF (vascular endothelial growth factor) by the glandular epithelium and induce apoptosis of endothelial cells (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Between October 2008 and February 2009, 50 consecutive patients (39 men and 11 women; age range, 29-80 years; mean age, 56 years) who satisfied the following inclusion criteria were enrolled in this retrospective study: (1) patients with histopathologically proven locally advanced rectal cancer ($T3 or regional lymph node involvement) at imaging; (2) patients who underwent post-CRT 3.0 T rectal MRI with DWI and post-CRT 18 F-FDG-PET/CT, followed by surgery. Surgery consisted of low anterior resection (n544), Mile's operation (n53), Hartmann's operation (n51) or transanal endoscopic microsurgery (n52).…”
Section: Patientsmentioning
confidence: 99%
“…The usefulness of DWI at 1.5 T in measuring treatment response has been measured in several clinical studies [13][14][15]. Recently, 3.0 T MR scanners have become commercially available [16][17][18]; the increase in signal-to-noise ratio (SNR) provided by these machines offers increased DWI quality and improvements to apparent diffusion coefficient (ADC) maps.…”
mentioning
confidence: 99%
“…Previous studies from other cancers have shown conflicting results 10 , 11 , 12 , 13 . In rectal cancer, Atkin et al (10) showed a negative correlation between normalKtrans values and MVD counts.…”
Section: Introductionmentioning
confidence: 96%